Comfortable climatic conditions for human on the territory of Ukraine for the period 1991—2020 - Boychenko, S.; Zabarna, О.; Kuchma, T. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2021)
The ecological state of the environment, climatic conditions with pronounced seasonality, variability, anomaly summer heat and regional manifestations of climate change, have a certain negative impact onwell-being, health and comfort of life of the population. To assess climatic comfort of a person, a bioclimatic index (equivalent-effective temperature) was used, which allows to evaluate thermal sensation of a person under a certain combination of meteorological parameters. In this study we used daily observation data (surface temperature, air humidity and wind velocity) at 34 meteorological stations in Ukraine for the period 1990—2020. Analysis and ranging of data, which characterize the thermal bioclimatic conditions, were done. It was found that the weather conditions with apparent temperature of very cold—cold—cool—slightly cool compose about 268 ± 9 (73 %) days per year. Thus, the population of Ukraine experience conditions of physiologically cold stress during the prevalent time of the year. Weather conditions that fall into gradations very cold –(30 ... 23) and cold –(23 ... 12) represent 6 ± 5 (~2 %) and 42 ± 17 (~12 %) days per year respectively. They can consequently cause extreme cold and strong cold stress and have a tendency towards decreasing repeatability. The largest number of days on average across the country have such gradations as slightly cool 0 ... 12 and cool –(12 ... 0), 113 ± 10 (31 %) and 107 ± 8 (29 %) days per year respectively. Slightly cool weather conditions are typical for the warm period of the year, mainly autumn and spring, and partially winter, while cool –(12 ... 0) is more prevalent in winter, autumn and spring seasons. Comfortable and subcomfortable thermal conditions for human with apparent temperature of slightly warm and warm compose on average 96 ± 8 (~26 %) days per year. Comfortable thermal conditions for human on the territory of Ukraine represent about 47 ± 13 (13 %) days per year and are typical for the warm period from April to October, with maximal values in summer: June 10 ± 3, July 17 ± 4 and August 15 ± 4 days per month. A number of days with subcomfortable thermal conditions for human on the territory of Ukraine compose also 48 ± 3 (13 %) days per year. Moreover, for May—September it has almost an equal number of days per month from 7 to 12 with minimal values in April, October and November, about 1—2 days. There is a tendency to increase in the number of days with comfortable thermal conditions for human in summer by 0.2—0.3 days per month for the period 1991—2020. The trend is 0.83 days per year (on average 25—30 days were added each year) for the period 1991—2020. Thus, comfortable climatic conditions for the local population in Ukraine increase during the warm season. However, the frequency of hot apparent temperatures (23 ... 30) has increased, especially during summer period, which can subsequently cause strong and extreme heat stress for humans. In particular years, it was recorded up to 5—19 days per year. For that reason, the climatic conditions of Ukraine have a certain potentially comfortable climatic resource(in June—August): Western region has a minimal climatic resource (23—40 %); Northern region has a sufficient climatic resource (36—53 %); Central region has an optimal climatic resource (40—60 %); Southern region has an optimal climatic resource (40—67 %).